PERSONALITY CIVIL CULTURE: THEORETICAL MODEL AND WAYS OF FORMATION - Qodirov Fazliddin Yuldoshovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
tasks such as formation of democratic principles, increase of socio –political activity of citizens, implementation of freedom of a person in practice, liberalization of political processes, improvement of multiparty system on the basis of democratic norms, increase of activity of public and non-governmental organizations in the life of a society are connected with civil culture by expressing universal values. If we recognize civil society as an opportunity to reveal a high civil culture, we understand that the spiritual maturity of citizens is a factor of complete understanding of the Democratic principle in such a society. Because in civil society, understanding a person at a higher level of value is directly characterized by how much each citizen understands the level of his culture and is loyal to it. In this article, opinions and comments on the theoretical model and ways of formation of the civil culture of a person are made.